Batas Etis Pemanfaatan Limbah Hutan sebagai Energi Terbarukan: Kajian Ekosentrisme dalam Konteks Biomassa di Indonesia - M. Kudsi Rosadi; Muhammad Sarjan (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
The global energy transition has encouraged the utilization of forest biomass, including residues such as branches, leaves, and deadwood, as renewable energy sources through co-firing schemes in Indonesia. However, existing policies remain dominated by techno-economic logic and tend to overlook fundamental ethical-ecological dimensions, particularly the intrinsic value and ecological functions of forest residues in maintaining ecosystem integrity. This study aims to analyze the ecocentrism perspective on the utilization of forest waste as renewable energy and to formulate an ethical framework for ecologically just forest biomass governance. The research employed a qualitative approach through a narrative literature review of 58 selected articles from the Scopus, Web of Science, Google Scholar, and ScienceDirect databases published within the last 5–10 years. Narrative thematic analysis identified four major themes: the intrinsic value of forest waste from an ecocentric perspective, the ecological functions of forest residues in nutrient cycling and habitat maintenance, the ethical-ecological risks of biomass utilization, and the ethical threshold framework for forest waste utilization. As its primary conceptual contribution, this study proposes the “Ecocentric Ethical Threshold” (EET) framework, consisting of five principles: sufficiency, regenerative integrity, minimum residue retention, ecological value-based certification, and intergenerational justice. This framework implies the need to recalibrate Indonesia’s biomass co-firing policies by integrating verified ecological thresholds as prerequisites for harvesting, ensuring that the energy transition does not compromise the integrity of Indonesia’s tropical forest ecosystems.